2009
DOI: 10.1093/eurheartj/ehp368
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of heart failure patients associated with good and poor response to cardiac resynchronization therapy: a PROSPECT (Predictors of Response to CRT) sub-analysis

Abstract: Sub-analysis of data from PROSPECT showed that gender, aetiology of HF, QRS duration, severity of HF, a history of VT, and the presence of baseline mechanical dyssynchrony influence clinical and/or LV reverse remodelling after CRT. Although integration of information about these characteristics would improve patient selection and counselling for CRT, further randomized controlled trials are necessary prior to changing the current guidelines regarding patient selection for CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
152
7
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(181 citation statements)
references
References 34 publications
12
152
7
10
Order By: Relevance
“…This therapy has been demonstrated less efficacious in very advanced stages of heart failure. 22 Concordantly, our data show that in patients with high TAPSE values, CRT is more effective and produces beneficial effects in both the left and the right ventricles.…”
Section: Discussionsupporting
confidence: 76%
“…This therapy has been demonstrated less efficacious in very advanced stages of heart failure. 22 Concordantly, our data show that in patients with high TAPSE values, CRT is more effective and produces beneficial effects in both the left and the right ventricles.…”
Section: Discussionsupporting
confidence: 76%
“…Although the PROSPECT trial showed modest sensitivity and specificity of echocardiographic parameters of dyssynchrony, 23 subanalysis including 286 patients from the original PROSPECT cohort that focused on three simple preprocedural measures of dyssynchrony reported a strong association of their parameters with more extensive reverse remodeling at 6-month follow-up. 24 LBBB is clearly more evident in early LVRR patients. 25,26 In our study, Groups B and C had a higher incidence of ischemic etiology.…”
Section: Discussionmentioning
confidence: 89%
“…Although multiple factors including NYHA class at baseline and etiology of heart failure are associated with LV reverse remodeling after CRT, as is also shown in a sub-analysis of the PROSPECT study, at the least, the presence of mechanical dyssynchrony between the septum and free wall at baseline should be a key indicator of LV reverse remodeling after CRT. 15 In contrast, the presence of LBBB was the strongest predictor of CRT benefit. The finding suggests that the presence of LBBB can predict the presence of mechanical dyssynchrony between the septum and free wall more accurately than present echocardiographic parameters.…”
Section: Intraventricular Dyssynchrony and Cardiac Remodeling After Crtmentioning
confidence: 93%